Penerapan Integrated Marketing Communication (IMC) Oleh Resto Bebek Joss Gandos Dalam Keberhasilan Buka Bersama Menggunakan Promo Paket Bukber Dan Berkah Ramadhan - Ananda Aulia Rechand; Luthfi Fakhressya; Ulfi Pristiana (Politeknik Kampar, 2023)
In the business world, not a few people use superior marketing strategies, one of which is imc as well as the Joss Gandos restaurant which uses an imc strategy that is no less superior to other culinary businesses. This research was made with the aim of finding out how the implementation of the IMC strategy was carried out at the Joss Gandos restaurant with a successful PAKET BUKBER and PAKET BERKAH. This research uses a qualitative method with constructivism paradigm as the basis. The study was conducted by two researchers with data collection techniques using in-depth interviews with Marketing Communication from Resto Joss Gandos as primary data and secondary data in the form of promo designs and promo recap results. The results of this study are that Resto Joss Gandos uses 8 kinds of IMC strategies, namely public relations & publicity, digital marketing, sales promotion, word of mouth, personal selling, event and experience, Point- of-Purchase Communication, and direct marketing. This strategy supports the success of Resto joss gandos in making promos, one of which is the buka Bersama promo with targeted results. In addition, resto joss gandos also uses IMC as an effort to align customers both online or on social media and those who come in person or dine in.